2013
DOI: 10.1111/jhn.12100
|View full text |Cite
|
Sign up to set email alerts
|

Food habits, socioeconomic status and body mass index among premenopausal and post‐menopausal women in Mauritius

Abstract: Background: Although many health disparities arise as a result of socioeconomic inequalities, less is known about the diet quality of women after menopause. The present study aimed to determine the factors affecting food habits and body mass index (BMI) among premenopausal and post-menopausal Mauritian working women. Methods: The study was conducted as a cross-sectional survey in different workplaces located in the nine districts of Mauritius. Mauritian women (n = 400; 215 premenopausal, 185 post-menopausal) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 25 publications
2
23
0
1
Order By: Relevance
“…Monteiro et al [50] reported that income level tends to be a risk factor for obesity while education may be protective as a higher level of income means a greater affordability for energy dense foods. However, in this study, a higher level of income was found to be related to a lower BMI which corroborates findings of Fokeena and Jeewon [51] and Bhurosy and Jeewon [52] where participants in high a socio-economic status (SES) group had lower BMI than those in a low SES group. Similarly, nutrition knowledge, positive nutrition attitude and greater fruit and vegetable intake were related to a lower BMI.…”
Section: Discussionsupporting
confidence: 91%
“…Monteiro et al [50] reported that income level tends to be a risk factor for obesity while education may be protective as a higher level of income means a greater affordability for energy dense foods. However, in this study, a higher level of income was found to be related to a lower BMI which corroborates findings of Fokeena and Jeewon [51] and Bhurosy and Jeewon [52] where participants in high a socio-economic status (SES) group had lower BMI than those in a low SES group. Similarly, nutrition knowledge, positive nutrition attitude and greater fruit and vegetable intake were related to a lower BMI.…”
Section: Discussionsupporting
confidence: 91%
“…Menopause, characterized by the end of female reproductive function, is presented as a factor that can contribute to weight gain. The aforementioned study in the Republic of Mauritius evidenced that being postmenopausal constituted a risk factor for obesity, compared to women in the pre-menopause period (18) .…”
Section: Discussionmentioning
confidence: 98%
“…A study conducted in the Republic of Mauritius showed that low socioeconomic status was a risk factor for obesity among the surveyed women (18) . In developed countries, obesity tends to be more prevalent among those with low incomes than those with high incomes.…”
Section: Discussionmentioning
confidence: 99%
“…16 The level of physical activities and the nutritional and dietary habits also affects the symptoms seen in the women. 17 The age of menopause is affected by biological symptoms like genetic, nutritional, and reproductive history; sociocultural symptoms like educational status, occupational status, mobility rural urban residence; and lifestyle like smoking habits and dietary habits. 18 There are better infrastructures and facilities available in urban areas than in rural areas.…”
Section: Discussionmentioning
confidence: 99%